AB0449 Radiographic change and time-course change in cytokine levels of rheumatoid arthritis patients on etanercept treatment. (23rd January 2014) - Suda, A.; Nagaoka, S.; Furukawa, H.; Thoma, S.; Ideguchi, H.; Ohno, S.; Ishigatsubo, Y.
Abstract : Objectives: To study changes in cytokine levels and radiographic findings (mTSS) in rheumatoid arthritis (RA) patients newly treated with etanercept (ETA). Methods: In our 19 pts who started ETA during Nov/2005 - Jan/2007 (2 men; mean age, 62.0 yo; mean disease duration, 8.7 yrs), cytokine (IL-4, IL-6, IL-8, TNFa) levels were determined at baseline, week 4, 24 to assess relationship of RA activity and radiographic findings. Results: Mean DAS28 (ESR) at baseline, & week 4, 24: 6.7, 5.0, 3.8 respectively. Compared to baseline, TNFaat week 24 significantly increased (2.3 vs 96.9). IL-6 significantly decreased (37.4 vs 9.73). Mean mTSS was 92±62 at baseline and 94±64 at week 24; 9 pts achieved radiographic remission (ΔmTSS ≤0.5). Analysis of factors affecting radiographic remission showed no significant variable of patient's background. Cytokine levels in the remission group appeared to be lower at week 24: IL-4 (91 vs 351), IL-6 (6.8 vs 12.4), IL-8 (5.0 vs 10.8), TNFa (91.0 vs 102.2), but no significant difference. Conclusions: We evaluated the relationship between radiographic remission and cytokine changes in the course of ETA treatment. Although the remission group had a decreasing tendency of IL-4, IL-6, IL-8, TNFaat week 24, no significant difference was seen. Disclosure of Interest: None Declared